Hazel Hill is gonna win this one - Horne, Maggie (2022)
"Seventh grader Hazel Hill is too busy for friends. No, really. She needs to focus on winning the school-wide speech competition and beating her nemesis, the popular and smart Ella Quinn, after last year's embarrassing hyperbole/hyperbowl mishap that cost her first place. But when Hazel discovers Ella is being harassed by golden boy Tyler Harris, she has to choose between winning and doing the right thing. No one would believe that a nice boy like Tyler would harass and intimidate a nice girl like Ella, but Hazel knows the truth, and she's determined to prove it, even if it means risking everything."--
008-012
Keywords: Bullying in schools -- Juvenile fiction; Conduct of life -- Juvenile fiction; Sexual harassment of women -- Juvenile fiction; Friendship -- Juvenile fiction; Middle school students -- Juvenile fiction; Contests -- Juvenile fiction; Bildungsromans; Fiction; Juvenile works; Novels; School fiction; Bildungsromans; School fiction; Novels